HD 89345: a bright oscillating star hosting a transiting warm Saturn-sized planet observed by K2 - Van Eylen, Vincent; Heeren, Paul (Arxiv, 2018)
We report the discovery and characterization of HD 89345b (K2-234b; EPIC 248777106b), a Saturn-sized planet orbiting a slightly evolved star. HD 89345 is a bright star